Implementasi KKL di Desa Muara Wahau: Pendidikan Agama, dan Pembentukan Karakter Pemuda - Astuti, Aprianti; Amanda Stevany Nurvita; Virda Bin Jusman; Fitri Handayani Depends; Afif Rahman; Lailatul Aisyah; Oktavia Amanda Putri Sunaryad; Febriana Nurhaliza; Muh Din Syamsulhadi; Zahrotun Ni’mah; Siti Nur Patimah; Muhammad Yahya Nuzulul Kurniawan; Rahmawati Rahmawati; Mahfud Ifendi; Jamila Iskandar (Lembaga Pengembangan Kinerja Dosen, 2026)
This study describes the implementation of Field Work Lectures (KKL) in Muara Wahau Village, focusing on religious education, youth character building, and community economic and social empowerment. KKL students were directly involved in teaching at the TPQ (Islamic Religious Education Center), tutoring for elementary and kindergarten students, leadership development in junior and senior high schools, mentoring MSMEs, community service activities, group exercise, and family health data collection. Data were obtained through observation, interviews, and documentation, then analyzed thematically. The results showed that the KKL successfully improved the youth's Quran reading skills, understanding of religious values, discipline, leadership, and social awareness. Furthermore, economic and social empowerment through MSME mentoring and community activities strengthened community independence and synergy. Obstacles such as high rainfall and the absence of the village head were successfully overcome through intensive coordination and adjustments to the activity schedule. The KKL proved effective as a practical learning tool for students while also having a positive impact on the community.